Des chevaliers de Charlemagne aux <<mercenaires>> du XIXe siècle - Bolcu, Amalia Maria (Études sur la Région Méditerranéenne, 2020)
Our communication’s purpose is to analyse the metamorphosis of characters embodying the soldier, as we can notice in literature (picturing the Franco-Prussian War) in relation to medieval texts. The first hypothesis from which we began our study focuses on the idea that in the two types of texts we can remark a visible degeneration of the literary representation of the soldier and of the ideal warrior. The second hypothesis is the fact that between the same category of characters we can also identify some correlations. The working method consists of the comparison between the two types of characters belonging to the very distant literary periods in order to find out what separate them and what are the similarities that bring them together. The explanations for their distinctive characteristics and their similarities will be researched both in literature and history. Our communication corresponds to the theme proposed by the colloquium, more specifically to the section that deals with the history of the nation in the late 19th century/literary representations of the nation.